Mapping International Collaboration and Research Hotspots in Educational Technology: A VOSviewer Analysis - Erry Hendriawan; Reni Marlina; Mohamad Heri Hadian; Iin Indra Nuraeni; Sun Sun Pradana Yogaswara (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Educational technology has become one of the fastest-evolving fields in global education research. However, disparities in international collaboration and thematic focus remain underexplored. This study aims to map global research trends, collaboration patterns, and emerging hotspots in educational technology over the past decade. A bibliometric analysis was conducted using data from the Scopus database, covering the period 2015â€“2024. The dataset included 2,850 documents consisting of journal articles and conference papers retrieved using the keywords â€œeducational technology,â€ â€œdigital learning,â€ and â€œe-learning.â€ Data were analyzed using VOSviewer 1.6.20 to visualize co-authorship by country and author, as well as keyword co-occurrence networks. The findings reveal four major collaboration clusters dominated by the United States (n = 742), China (n = 533), United Kingdom (n = 417), Spain (n = 248), and India (n = 220). Keyword analysis shows a thematic shift from blended learning and MOOCs (pre-2020) to online learning and COVID-19 education (2020â€“2022), followed by AI in education, learning analytics, and digital literacy (2022â€“2024). Six main author clusters were identified, though collaboration density remains low (0.25). Indonesia contributed 74 publications, mainly collaborating with Malaysia, Australia, Japan, and the United Kingdom, indicating an emerging but developing research role. Global educational technology research remains concentrated in developed countries, yet participation from Asia particularly Indonesia is growing. The results highlight the need for stronger international collaboration, methodological improvement, and inclusive research ecosystems to ensure equitable development in digital education scholarship.